0!=0^2, therefore 0=0^2+-C
that is: nothing is not no nothing.
This has even logical false to false is true parity, meaning one would want to believe it to be true.
So if it wasn't no nothing, but was not nothing (as in anything) and some C, then this something could be the "anything" and they could cancel to be nothing. Thus proving 0=0^2+-C.

2=1

1=1+1

1=(1+1)+(1+1)

2x=1x, x = 0

0=0+0

0=(0+0)+(0+0)

0=2*0=4*0=16*0=256*0=65536*0=4294967296*0=3.40282366921*10^38*0

2*0=o^2

0^2=1, since not nothing is something, 0*0 likely equals 1 as if you didn't have 0 cars in your driveway maybe you have one.

Subtract 1 from both sides to get: 0^2-1=0, x^2-1=x

0 has a creative stability factor at Phi, 1.618 or -.618!

Similarly the Fibonacci numbers are,

Loop:

a=a+b

b=b+a

Solving this system of equations we get

a=b

a=2*a

a=0

b=0

Such that solved form of the Fibonacci numbers is:

0=0+0

In The Beginning He was! From 0^2=1, there is another step you can take:

0^2/0=1/0

0=1/0

Now since 0=-0

0=1/-0 or 0=-1/0

substitute x for 0 and you have:

x = -1/x

this is the definition of i, the imaginary unit and is the step that differentiates the heart from the face; the Mandelbrot to Manny step is that the real part of x in x=x^2-c equals -1/real. This is meaningful as -1/1.618=-.618 and -1/-.618=1.618

Speaking of differentiation:

0-0=0^2=x=anything=1 because 0 removed from 0 would leave zero of zero. As Christ Jesus said, those who have not will have even what they have taken away. Now for infinity: if you had infinity squared and added nothing to it, it would be equal to infinity plus c because the derivative of x^2 approaches infinity as x approaches infinity. Meaning an infinitesimal increase would yield definite gains. (oo+0)**2=oo+c. Subtract one from both sides and let the 0 vanish and you get the same equation again oo^2-c=oo! As dividing by 0 = 1/oo, oo/0 = oo^2 and since you can always add a zero oo/0=1.618.....!